1999
DOI: 10.1016/s0014-5793(99)00345-2
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoazurin mediates periplasmic electron flow in a mutant strain of Paracoccus denitrificans lacking cytochrome c550

Abstract: A periplasmic protein able to transfer electrons from cytoplasmic membrane to the periplasmic nitrite reductase (cytochrome cd 1 ) has been purified from the anoxically grown cytochrome c 550 mutant strain Pd2121 and shown to be pseudoazurin by several independent criteria (molecular mass, copper content, visible spectrum, N-terminal amino acid sequence). Under our assay conditions, the half-saturation of electron transport occurred at about 10 W WM pseudoazurin; the reaction was retarded by increasing ionic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 14 publications
3
14
1
Order By: Relevance
“…Thus, either cytochrome c 550 or pseudoazurin is required for one, or most probably the only, step of the electron transfer pathway from the cytochrome bc 1 complex to cytochrome cd 1 . This conclusion is in agreement with the recent report that addition of pseudoazurin stimulated the rate of electron transfer from succinate to nitrite in rightside-out vesicles, which must have retained externally bound cytochrome cd 1 -type nitrite reductase, from cytochrome c 550 -deficient P. denitrificans (23). A previous proposal (28) that one or more additional c-type cytochromes act as alternatives to cytochrome c 550 in electron transfer to nitrite reductase is not supported by the present work.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, either cytochrome c 550 or pseudoazurin is required for one, or most probably the only, step of the electron transfer pathway from the cytochrome bc 1 complex to cytochrome cd 1 . This conclusion is in agreement with the recent report that addition of pseudoazurin stimulated the rate of electron transfer from succinate to nitrite in rightside-out vesicles, which must have retained externally bound cytochrome cd 1 -type nitrite reductase, from cytochrome c 550 -deficient P. denitrificans (23). A previous proposal (28) that one or more additional c-type cytochromes act as alternatives to cytochrome c 550 in electron transfer to nitrite reductase is not supported by the present work.…”
Section: Discussionsupporting
confidence: 93%
“…In the presence of copper, however, the mutation in the gene encoding cytochrome c 550 had hardly any effect on the denitrifying potential of that mutant strain, indicating that a copper-dependent electron carrier substituted for cytochrome c 550 (51). A likely candidate is pseudoazurin, which is a type I blue copper protein and able to mediate electron transfer between the cytochrome bc 1 complex and the nitrite, nitric oxide, and nitrous oxide reductases in vitro (21,25,26). Indeed, it has been shown that a mutant strain deficient in cytochrome c 550 and pseudoazurin failed to reduce nitrite (30;Stuart Ferguson,unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…The physiological electron donors of P. denitrificans N 2 OR have long been established to be cytochrome c-550 and pseudoazurin [20,21]. In the first case, the docking simulation gave several solutions in the top 200 of each ranking with a favorable orientation for electron transfer ( Fig.…”
Section: General Analysismentioning
confidence: 99%
“…A steady-state kinetic study demonstrated that the interaction between the two proteins is mainly hydrophobic in nature and that mitochondrial cytochrome c is not a competent electron donor to this enzyme [18]. On the other hand, N 2 OR isolated from Paracoccus pantotrophus, an organism closely related to P. denitrificans, can accept electrons from cytochrome c-550 and pseudoazurin [19][20][21], and also from the mitochondrial cytochrome c [22]. A structural model for the electron transfer complex between P. denitrificans N 2 OR and either P. panthotropus cytochrome c-550 or P. panthotropus pseudoazurin has been proposed on the basis of a theoretical docking study [23].…”
Section: Introductionmentioning
confidence: 99%